Analysis of Hydrogen-Induced Changes in the Cyclic Deformation Behavior of AISI 300–Series Austenitic Stainless Steels Using Cyclic Indentation Testing - Sven Brück; Bastian Blinn; Katharina Diehl; Yannick Wissing; Julian Müller; Martina Schwarz; Hans-Jürgen Christ; Tilmann Beck; Thorsten Staedler; Xin Jiang; Benjamin Butz; Stefan Weihe (Metals, 2021)
The locally occurring mechanisms of hydrogen embrittlement significantly influence the fatigue behavior of a material, which was shown in previous research on two different AISI 300-series austenitic stainless steels with different austenite stabilities. In this preliminary work, an enhanced fatigue crack growth as well as changes in crack initiation sites and morphology caused by hydrogen were observed. To further analyze the results obtained in this previous research, in the present work the local cyclic deformation behavior of the material volume was analyzed by using cyclic indentation testing. Moreover, these results were correlated to the local dislocation structures obtained with transmission electron microscopy (TEM) in the vicinity of fatigue cracks. The cyclic indentation tests show a decreased cyclic hardening potential as well as an increased dislocation mobility for the conditions precharged with hydrogen, which correlates to the TEM analysis, revealing courser dislocation cells in the vicinity of the fatigue crack tip. Consequently, the presented results indicate that the hydrogen enhanced localized plasticity (HELP) mechanism leads to accelerated crack growth and change in crack morphology for the materials investigated. In summary, the cyclic indentation tests show a high potential for an analysis of the effects of hydrogen on the local cyclic deformation behavior.